2018
DOI: 10.1007/s00248-018-1190-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Succession Decreases Network Complexity During Plant Material Decomposition in Mangroves

Abstract: In this study, 16S rRNA gene amplicon sequencing was used to assess bacterial diversity and dynamics throughout different stages of leaves decomposition of three plant species (Rhizophora mangle, Laguncularia racemosa, and Avicennia schaueriana) in three distinct mangroves of São Paulo state, Brazil. The experiments were conducted in microcosms. Phylogenetic diversity (Faiths' PD) index showed differences between samples and suggested that some treatments like R. mangle increased their bacterial diversity thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Environmental dynamics pose a challenge to the survival of nutrient cycling organisms in estuarine environments ( Holguin, Vazquez & Bashan, 2001 ). In the case of mangroves, sediments can be dry or submerged as well as subjected to fresh or marine environments ( Bouillon et al, 2004 ), which results in a complex microbial assemblage ( Freschet et al, 2013 ; Miura et al, 2015 ; Moitinho et al, 2018 ). In this study, we have applied litterbag experiments to unravel the effects that plant species has on the microorganisms that colonize their decaying leaves and to identify how the environmental characteristics affect this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental dynamics pose a challenge to the survival of nutrient cycling organisms in estuarine environments ( Holguin, Vazquez & Bashan, 2001 ). In the case of mangroves, sediments can be dry or submerged as well as subjected to fresh or marine environments ( Bouillon et al, 2004 ), which results in a complex microbial assemblage ( Freschet et al, 2013 ; Miura et al, 2015 ; Moitinho et al, 2018 ). In this study, we have applied litterbag experiments to unravel the effects that plant species has on the microorganisms that colonize their decaying leaves and to identify how the environmental characteristics affect this process.…”
Section: Discussionmentioning
confidence: 99%
“…In each of these mangroves, fresh and mature leaves (at the same phenological state) from the three main species of mangrove trees ( Rhizophora mangle, Laguncularia racemosa, and Avicennia schaueriana ) were sampled directly from the tree. The chemical composition of these leaves varies between species, R. mangle has the lowest hemicellulose and protein content and the highest lignin content, L. racemosa has the highest hemicellulose, and the lowest cellulose content while A. schaueriana has the highest cellulose and protein content (see Moitinho et al, 2018 for details). Field sampling was approved by the Biodiversity Authorization and Information System (SISBIO #20366-3).…”
Section: Methodsmentioning
confidence: 99%
“…Environmental dynamics pose a challenge to the survival of nutrient cycling organisms in estuarine environments (Holguin, Vazquez & Bashan, 2001). In the case of mangroves, sediments can be dry or submerged as well as subjected to fresh or marine environments (Bouillon et al, 2004), which results in a complex microbial assemblage (Freschet et al, 2013;Miura et al, 2015;Moitinho et al, 2018). In this study, we have applied litterbag experiments to unravel the effects that plant species has on the microorganisms that colonize their decaying leaves and to identify how the environmental characteristics affect this process.…”
Section: Discussionmentioning
confidence: 99%
“…The use of network analysis has unveiled the relationships between populations and functions in the most diverse processes and habitats (Faust of mangrove trees (Rhizophora mangle, Laguncularia racemosa, and Avicennia schaueriana) were sampled directly from the tree. The chemical composition of these leaves varies between species, R. mangle has the lowest hemicellulose and protein content and the highest lignin content, L. racemosa has the highest hemicellulose, and the lowest cellulose content while A. schaueriana has the highest cellulose and protein content (see Moitinho et al, 2018 for details).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms in mangroves are important. Universal studies on the structure and diversity patterns of microorganisms in mangrove sediments and leaves, including the communities of bacteria [5][6][7], archaea [7,8], and fungi [9][10][11], have shown that the microorganisms in mangroves are important element cyclers and nutrient providers, thus elucidating the microbial roles for mangrove ecological functions. As we know, comprehensive information for the biotic and abiotic processes across space and time needs to be established to fully understand ocean ecosystems [12].…”
Section: Introductionmentioning
confidence: 99%